The impact of physique on strategy and performance in the 400 m hurdles race among elite male athletes - Janusz ISKRA; Subir GUPTA; Krzysztof PRZEDNOWEK; René V. BEST; Arkadiusz STANULA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2024)
Introduction: the objective of this study was to assess the impact of physique on the stride pattern and performance of elite male 400-m hurdles runners. Materials and Methods: this study is based on the analysis of the performance of 297 male 400-m hurdlers in 13 Olympic games, 16 world championships, and 15 European championships. The hurdlers were divided into 4 groups, based on their height and body mass index (BMI) - taller and heavier (TH), taller and lighter (TL), shorter and heavier (SH), and shorter and lighter (SL). Times taken to complete various phases of the 400m hurdles race - H0-1 (from starting line to hurdle 1), H1-3 (from hurdle 1 to hurdle 3), H3-5, H6-8, H8-10, and H10-F (from hurdle 10 to the finishing line) - were noted. Similarly, the number of strides to complete 3 inter-hurdle phases (H1-4, H4-7, and H7-10) was recorded. Results: The technical index (TI = time for 400m hurdles run - time for 400m flat run) was the lowest in TH, followed by TL, SL, and SH. The stride number increased from H1-4 to H7-10. Taller hurdlers took fewer strides than shorter ones. Only 8.5% of the hurdlers followed a uniform stride number (13 or 15). Conclusions: the physique of elite 400-m men hurdlers can vary widely. Taller hurdlers fly over hurdles more efficiently; a uniform stride pattern is independent of height and BMI, and is followed by a few hurdlers only, and physique has a significant impact on running performance at a few phases of the 400-m hurdles run.